Protection against traffic noise in urban areas in relation to noise control plans - Bohatkiewicz, Janusz (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
Exposure to traffic noise belongs to the most harmful impacts affecting people who live in towns. Nearly one third of residents of big towns in Poland suffers from permanent exposure to traffic noise, which may have adverse effects on health. The same refers to most European cities. The problems of noise is regulated by identical legislation in the EU and in Poland. Noise control in big towns arises from regulations related to obligatory provision of noise mapping and noise control plans. The plans contain, among other things, site-specific methods of protection against traffic noise. Those sites are defined by means of the “M” index, whose value is the higher the more people live in the area and the more permissible noise levels are exceeded. The noise control plans prepared to-date contain a range of methods and measures aimed at ensuring protection against traffic noise. In many cases those methods are nothing but improvised response and are not effective enough in towns, for example noise barriers. Results of pilot research indicates that comprehensive physical traffic calming measures may prove to be an effective and long lasting noise control solution in the surrounding of streets in urban areas. Physical traffic calming may be more effective than the measures commonly used so far which does not require additional land acquisition.